Can Islamic banking and finance spur financial inclusion? Evidence from Sub-Saharan Africa - Musa Abdu; Adamu Jibir; Salihu Abdullahi; Aliyu A. Rabi'u (CBN Journal of Applied Statistics, 2018)
This study examined the effect of introduction of Islamic banking and finance on financial inclusion in Sub-Sahara Africa (SSA). To achieve this objective, the study applied Probit, Tobit and Juhn-Murphy-Pierce decomposition to estimate model of financial inclusion. The study used World Bank's Global Financial inclusion index (Global Findex) dataset of 2015. The findings revealed that the introduction of Islamic banking and finance system in some Organization of Islamic Cooperation (OIC) countries in SSA enhanced financial inclusion in the sub-region. The study also uncovers that households from OIC with Islamic banking and finance are more likely to be financially included than their counterparts in OIC countries without Islamic banking and finance. Further, there are other factors that play an important role in determining the probability of financial inclusion in the region. Inter alia, these factors include age, gender, income level and level of education. The policy implication of the findings is that introducing Islamic banking and finance is necessary for spurring financial inclusion in OIC of SSA.
Keywords: G10; G20; Z12; C14; O55; C35; 330; Financial inclusion; Islamic banking; Juhn-Murphy-pierce; OIC; Sub-Saharan Africa; Tobit